Oil Characterization of Four Indigenous Albanian Olive Cultivars - Topi, Dritan (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
One of the evergreen plants in the Mediterranean environment is the olive tree. Situated in the Northern Mediterranean, Albania possesses a significant proportion of arable land planted by this tree. Olive trees are grown in the western and southern portions of the country, alongside the Ionian and Adriatic Seas, characterized by a Mediterranean climate. Twenty-two native olive cultivars have been classified via their genetic profile. The potential of olive oil production using native cultivars as the primary source gives the country a significant opportunity to distinguish its olive oils (OO). Among them, Kalinjot and Nisiot, two unique native cultivars grown mostly in southern regions, present significant promise. Their OO chemical characterization is distinguished when compared with two other native cultivars, Ulli i bardhë Tirana (Bianco di Tirana) and Mixan, domesticated in central regions. Regarding fatty acid profiles, there is a significant difference in oleic acid, with Nisiot (80.07 ± 0.04%) higher than Mixan OO (71.91 ± 0.06%). On the other hand, variations in Linoleic acid showed higher differences among two cultivars from the same region, Nisiot (4.10 ± 0.00%) and Kalinjot (10.11 ± 0.01%). The phenolic compounds content in OO show that Ulli i bardhë Tirana cv, referring to Gallic acid equivalent (GAE), is 445.03±16.83 mg GAE/kg, is higher compared to the two cultivars, Kalinjot (216.63±10.76 mg gallic acid/kg) and Nisiot (275.45± 11.63 mg GAE/kg). The latest trends in olive cultivation toward international olive cultivars present an essential and delicate situation for the future of indigenous cultivars, both to preserve the genetic diversity, as well as nutritional and organoleptic characteristics of Albanian OO. Globalization has influenced olive cultivation by exposing indigenous olive cultivars to distinguished cultivars worldwide. Promoting the OO from indigenous olive cultivars needs more profound research to enable and highlight the advantages and disadvantages of persisting the tradition of indigenous olive cultivars cultivation.